Потревоженные тени - Терпигорев Сергей Николаевич (Сов. Россия, 1988)
Экземпляры: Селтинская районная библиотека (к/х) (20200610) / Инвентарный номер: 132988 / Цена: / Авт.знак: Т 35 / ГРНТИ: 17.82.30 / ББК: 84(2Рос=Рус)1